Strengthening the global competitiveness of halal culinary SMEs in North Sumatra through a Maqasid of Shariah-based approach‎ - Ismail, Ismail; Tarigan, Azhari Akmal; Soemitra, Andri; Nawawi, Zuhrinal M. (Universitas Islam Indonesia, 2025)
IntroductionThe global halal food industry, projected to reach USD 2.4 trillion by 2024, presents a substantial opportunity for regional economies such as North Sumatra. Despite the region’s rich culinary heritage, the development of its halal culinary industry faces critical challenges, including limited access to halal certification, low levels of product innovation, and inadequate adoption of digital marketing strategies. These limitations hinder the competitiveness of local small and medium enterprises in the creative economy sector.ObjectivesThis study aims to formulate a strategic development model for North Sumatra’s halal culinary industry using a values-based approach grounded in Islamic economic principles. It specifically integrates the Maqasid of Shariah framework as a benchmark for ethical and sustainable development.MethodThe research employed a qualitative methodology through in-depth interviews with ten key stakeholders, including halal culinary entrepreneurs, government agencies, academics, and religious institutions. Data were analyzed using Atlas.ti version 9 to identify key development issues, which were then evaluated using the Maqasid of Shariah Index. The model assessed three main dimensions: Tahdzib Al-Fard (individual education), Iqomat Al-Adl (justice), and Maslahah (public welfare).ResultsFindings identified digital marketing, product development, capital access, and halal certification as top strategic priorities. The Maqasid of Shariah Index score reached 67.90%, categorized as “Fairly Good.” Among the dimensions, individual development scored the highest, followed by justice and public welfare. This highlights the significance of capacity building and ethical governance in improving the industry's competitiveness.ImplicationsThe integration of qualitative analysis with the Maqasid of Shariah Index provides a structured and ethical framework for policy-makers and business actors. The findings offer practical guidance for implementing strategies that are both economically viable and religiously aligned, enabling inclusive and sustainable growth in the halal culinary sector.Originality/NoveltyThis study introduces an innovative model by combining a qualitative data analysis tool with a syariah-based evaluative index, a method rarely applied in the development of creative halal industries. It offers new insights into ethically grounded strategic planning for regional halal economic development.